Birch pollen immunotherapy inhibits anaphylaxis to the cross‐reactive apple allergen Mal d 1 in mice. Issue 11 (8th August 2016) - Utsch, L.; Logiantara, A.; Wallner, M.; Hofer, H.; van Ree, R.; van Rijt, L. S.
Summary: Background: Cross‐reactive apple allergy is a common co‐morbidity of birch pollen allergy, caused by the presence of a Bet v 1 homologue allergen in apple, Mal d 1. Treatment of tree pollen hay fever by immunotherapy is well established, but its effect on the accompanying apple allergy is debated. Objective: To establish a mouse model of birch pollen induced cross‐reactivity to Mal d 1 and investigate the effect of birch pollen immunotherapy on the cross‐reactivity to Mal d 1. Methods: Respiratory allergy was induced in Balb/c mice by intraperitoneal exposure to alum‐adsorbed birch pollen extract (BPE) in combination with short or prolonged intranasal exposure to BPE. To evaluate the response to Mal d 1, mice were exposed intraperitoneally to Mal d 1. Immunoglobulin responses and cytokine production by splenocytes were measured by ELISA. Allergic symptoms were evaluated by measuring airway hyper‐reactivity and hypothermia as a surrogate marker for anaphylaxis. Immunotherapy was performed subcutaneously with alum‐adsorbed BPE. Results: Mice exposed to BPE develop cross‐reactive IgE to Mal d 1. Early after exposure to BPE, this response is still weak and does not yet translate into anaphylaxis. Interestingly, later re‐challenge with BPE increased cross‐reactivity to a level where Mal d 1 exposure induced anaphylaxis. Cross‐sensitization can also be induced by systemic Mal d 1 exposure. Birch pollen immunotherapy significantly reduced the anaphylactic response of mice to Mal d 1. Conclusion & Clinical Relevance: A mouse model mimicking birch pollen induced cross‐reactivity to Mal d 1 was successfully established. In this model, birch pollen immunotherapy significantly ameliorated the anaphylaxis induced by Mal d 1. Our experimental data suggest that boosting of Mal d 1 recognizing immunoglobulins by BP SCIT is important for the amelioration of apple allergy in human.